Thismia petasiformis (Thismiaceae), a new fairy lantern species from the Brazilian Amazon Forest - Ferreira Da Silva, Diego; Alvarenga Braga, João Marcelo (Phytotaxa, 2022)
Thismia petasiformis is described and illustrated as a new achlorophyllous mycoheterotrophic species discovered in the Brazilian Amazon Forest. The species belongs to Thismia subg. Ophiomeris sect. Pyramidalis by the presence of horizontal cylindrical roots, terete stem with scattered leaves, pyramidal stigma, and stamens flattened with connective not dilated, interstaminal lobes absent and ovary with parietal placentation from the base to the top of the ovary. Thismia petasiformis differs from T. fungiformis by the perianth tube apparently trigonous with slightly curved sides, annulus inconspicuous, and inner perianth lobes forming a single hat-shaped mitre. We present a taxonomic treatment for T. petasiformis, with a detailed description, illustrations and a preliminary assessment of its conservation status following IUCN categories and criteria.